Paediatric vocal fold nodules: management strategies to restore normal phonation—Speech-Language Pathologists perspective: A cross-sectional survey - Iqbal, Mariya; Mumtaz, Nazia; Saqulain, Ghulam; Iftikhar, Nayab (Journal of the Pakistan Medical Association, 2022)
Vocal fold nodules are benign vocal cord lesions which develop in voice abusers, including children, though chronic cough, sinusitis, and reflux may also be the causative agents. Since low or no-evidence treatment strategies, like the boone technique, are in use in paediatrics, this study was conducted to determine the treatment strategies used by speech-language pathologists in paediatric vocal fold nodules using a cross-sectional survey at Riphah International University, Lahore, from October 2016 to May 2017. Sixty-five speech-language pathologists working with children in private clinics and multidisciplinary settings were recruited using purposive sampling. A self-structured questionnaire was used for data collection. Analysis using SPSS -18 revealed that a combination of voice therapy and vocal hygiene was the most favoured treatment used by 65 (100%) speech-language pathologists, followed by 58 (89.2%) who also favoured respiratory and relaxation exercises, and 56 (86.2%) who also included parental counselling. Hence, a combination of voice therapy and vocal hygiene is a good therapeutic technique being practiced by speech pathologists for the treatment of vocal nodules among paediatric population. Keywords: Paediatric Population, Vocal Nodules, Vocal Hygiene, Voice Therapy.